First records of the invasive rotifer Kellicottia bostoniensis Rousselet, 1908 in different ecosystems of Colombia - Villabona-González, Silvia Lucía (2022)
Kellicottia bostoniensis (Rousselet, 1908) is a planktonic rotifer, native from North America, but reported in Europe, Asia and South American countries such as Brazil and Argentina, where is registered as invasive species. In zooplankton sampling carried out in the photic zone of different Colombian ecosystems (urban wetlands, reservoirs and rivers) between 2019 and 2022, individuals belonging to this species were recorded. This work is the first report in both Colombia and the North of South America, expanding its distribution range in the continent. The analyzed specimens show the typical morphological and morphometric characteristics of the K. bostoniensis species and a distribution in a wide range of environmental conditions, as it has been reported in other regions. Its invasive potential and the possibility that its distribution range expands towards other basins and ecosystems in Colombia and other countries of South America.